Perancangan Embung Baturetno Kapanewon Banguntapan Kabupaten Bantul - Amos Setiadi; Floriberta Binarti; Eddy Harsowibowo; Mimin Aminah Yusuf; Tri Suyud Nusanto (Jurnal Atma Inovasia, 2026)
Community Service is carried out to assist the community in procuring the design of the Baturetno reservoir as one of the natural tourist destinations in Kapanewon Banguntapan. The expected results of this activity are an increase in the number of tourist visits, especially domestic tourists, and its impact on the welfare of the local community. Community service is carried out in four stages: the preparation stage, the data collection stage, the location survey and interview stage, and the design and report-making stage. The final result of this activity is a picture album of the Baturetno reservoir, which includes the entrance gate, parking area, garden and gazebo, toilet, culinary area, pendhapa, and reservoir. The approach used in this activity is Community Participation, which is carried out through the Preparation, Implementation, and Utilization stages. The preparation stage includes coordination with the Tourism Office. The implementation stage consists of the identification of village potential data carried out in collaboration with Baturetno village partners. At the same time, the utilization stage includes the application of design in development activities. This Community Service activity also aims to encourage the community to increase the tourist attraction of Baturetno village